A exploração do nióbio no Brasil no contexto do novo imperialismo - Moscatiello, Giovanna Queiroz [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The historical geography of the capitalist method of production demonstrates how the system is organized throughout structural crises in the course of time. In this sense, to understand the operation and the most recent phase of capitalism, it is required to apply logic of accumulation based on the depredation and spoliation of natural and social resources. As stated by Lenin (1916) capitalism would have been transformed into capitalist imperialism by the end the century, in which the domination of financial capital through the constitution of productive/economic monopolies prevails. For Harvey (2004), capitalist imperialism reveals to us the contradiction between capital and state-territorial logics, with the former prevailing with excellence in the era of the so-called New Imperialism. In this work we intend to analyze how the Niobium extraction activity in Brazil is configured by capitalist exploitation in territories not yet included in this logic or under colonialist practices. The latter now known as Accumulation by Spoliation

A geografia histórica do modo de produção capitalista nos demonstra como, ao decorrer do tempo histórico, o sistema se organiza através de crises estruturais. Deste modo, entender o funcionamento e a fase mais recente do capitalismo pressupõe aplicar a lógica de acumulação precisamente pautada na depredação e espoliação dos recursos naturais e sociais. Como afirma Lênin (2011), na virada do século, o capitalismo teria se transformado em imperialismo capitalista, em que predomina o domínio do capital financeiro através da constituição de monopólios produtivos/financeiros. Para Harvey (2004), o imperialismo capitalista nos revela a contradição entre a lógica do capital e a lógica estatal-territorial, ainda que a do capital prevaleça com excelência na era do chamado Novo Imperialismo. De todo, neste trabalho, pretendemos analisar como a atividade de extração do Nióbio no Brasil obedece um molde que configura a exploração capitalista mediada através da reorganização de territórios ainda não inseridos nessa lógica ou que obedecem práticas de cunho colonialista, hoje denominadas como Acumulação por Espoliação
Keywords: Nióbio; Imperialismo; Geografia histórica; Capitalismo; Brasil